A Systematic Review of Psychosocial Barriers and Facilitators to Smoking Cessation in People Living With Schizophrenia - Lum, Alistair; Skelton, Eliza; Wynne, Olivia; Bonevski, Billie (Frontiers in Psychiatry, 2018)
Background: People living with schizophrenia are less likely to quit smoking compared with the general population and people living with other psychiatric disorders. Understanding the psychosocial barriers to smoking cessation is important for designing effective smoking cessation interventions. We aimed to systematically review research examining psychosocial barriers to smoking cessation in people living with schizophrenia. Methods: We followed the PRISMA statement to conduct a systematic literature review examining psychosocial barriers to smoking cessation in people living with schizophrenia. We searched EMBASE, Medline, PsycINFO, and CINAHL databases from inception to 14 June 2018 to identify relevant articles. We included peer-reviewed original research articles that examined psychosocial barriers to smoking cessation, as well as factors associated with maintenance of smoking habits in people living with schizophrenia spectrum disorders. Qualitative, quantitative, or mixed-methods study designs were included. Three authors screened titles, abstracts, and full-texts using the eligibility criteria. We conducted a narrative synthesis of the data to account for the heterogeneity of study designs. We analyzed qualitative and quantitative studies separately. Results: We identified 685 studies from our systematic search and screened the full-text of 134 articles. The final set of articles included 24 articles, of which 21 had quantitative designs and 3 had qualitative designs. The most commonly cited barrier to smoking cessation in people living with schizophrenia was cravings and addiction, followed by a perceived increased risk of negative affect associated with quitting smoking. People living with schizophrenia reported smoking to manage stress and to maintain social relationships, reducing their likelihood of quitting. People living with schizophrenia were found to be less likely to receive cessation support from health professionals than smokers without schizophrenia. Conclusions: Overall, it appears that people living with schizophrenia experience a wide range of barriers to smoking cessation. The influence of these barriers on smoking cessation likelihood may be greater among people living with schizophrenia than people without psychiatric disorders. Health professionals play an important role in smoking cessation for people living with schizophrenia and should support quitting in this vulnerable population. The barriers identified in this review can inform the development of targeted smoking cessation interventions.